An indigenous design of Integrated Automated Current Weather Instruments System (IACWIS) for aeronautical meteorological observations - BIJU, PS; MALI , RR; VASHISTHA, RD (MAUSAM, 2008)
There is an urgent need for modernisation of aeronautical meteorological instruments considering the exponential growth of aviation industry in India. As a part of modernization, an attempt has been made by the authors to design and develop an Integrated Automated Current Weather Instruments System (IACWIS) for the continuous monitoring of wind direction and speed, temperature and dew point at the touchdown zone of the runway. This system being digital has a lot of advantages such as vector averaging for wind direction and wind speed, data archival and amenable for further analysis etc. The system after successful field trials has been installed at seven international airports in the country (Bangalore, Calicut, Diu, Hyderabad, Lucknow, Nagpur and New Delhi). The system meets the operationally desirable accuracy requirements of International Civil Aviation Organisation (ICAO, 2004) and vector averaging of wind data as recommended by World Meteorological Organisation (WMO, 1992). The system design capabilities and scope for expansion have been presented in this paper.